Second language (L2) production a conceptual framework of metacognitive attributes in on-line speech and language performance - Salaya, Thea Lyn D
Understanding the nature of the processing demands of speaking in L2 ss of theoretical and pedagogical interest. Unfortunately, information on the nature of the thinking processes during on-line L2 performance is still scarce in the psycholinguistics and cognitive linguistics literature. While there are certainly hosts of non-cognitive factors providing insights on the hesitance of L2 speech, it is also imperative to approach the understanding of second language production through the cognitive, information-processing lens as speaking is fundamentally a complex mental phenomenon. The cognitive perspective on second language production assumes that speaking is under the constraints of the working memory capacity. current literature presents that this limitation is task-specific is inhibitory of simultaneous attention allocation and is demanding of self-regulatory controlled processing. There is a standing assumption that different tasks pose different cognitive and metacognitive processing demands to regulate performance. As a consequence, the quality of speaking performances varies depending on the task being performed. This descriptive qualitative research thus aimed to explore the different metacognitive attributes that can be found present during on-line speech and language performance. Participants included a total of 10 AB-English students who were subjected to an impromptu speaking task. The quality of their performances was assessed through the use of the general indices of complexity, accuracy, and fluency. An oral reflection of the participants on their performance, through a guided interview, was then collected and analyzed through deductive and template thematic analysis to find answers to the metacognitive attributes observed during task performance. t was found that participants exhibited diversity in terms of their speaking proficiency, and there are variations in the characteristics of speech in different proficiency levels. The participants also demonstrated the use of metacognitive attributes of understanding interaction, and control, regardless of their proficiency level, to facilitate their impromptu speaking performance. Out of these attributes, frameworks were generated to illustrate the metacognitive processes that have emerged in each proficiency level. Finally, based on these different frameworks, a conceptual model for the metacognitive attributes present during L2 speech and language production in an impromptu speaking task was generated. These findings present theoretical, practical, and pedagogical implications on optimizing the pedagogy of speaking in an L2 classroom, with English as a second language .